Synthetic Circular gRNA Mediated Biological Function of CRISPR-(d)Cas9 System - Wang, Mingxia; Xu, Jinming; Meng, Jialin; Huang, Xinbo (Frontiers in Cell and Developmental Biology, 2022)
Ever since the gene editing function was discovered in the CRISPR-Cas9 system, numerous applications and utilities were investigated in order to apply this technique to medical use. However, the clinical practice was limited by unsatisfactory efficiency and unacceptable off-target editing. Modifications from different aspects of the Cas9 protein and gRNAs were published that aimed to improve its function in one way or another. Under the inspiration of Jacob L. Litke and Samie R. Jaffrey, we propose a novel gRNA design that could achieve rapid circular gRNA assembly inside the cells. This circular design consists of the gRNA of interested flanked by Twister ribozymes. The function of this circular gRNA was proved in vitro in both CRISPR-dCas9 and CRISPR-Cas9 systems. It presented a remarkable reduction in the off-target rate in accompany with reduced efficiency. With future improvement in its efficiency, this tool broadens our understanding and possibility of the CRISPR application.